2003
DOI: 10.1046/j.1523-1747.2003.12401.x
|View full text |Cite
|
Sign up to set email alerts
|

Terfenadine Antagonism Against Interleukin-4-Modulated Gene Expression of T Cell Cytokines

Abstract: Here, we investigated whether an anti-allergy drug, terfenadine, affects interleukin-4-modulated cytokine expression in peripheral T cells. Peripheral blood T cells were first stimulated with recombinant interleukin-4 and then tested for modulation of the mRNA of a panel of cytokines using the reverse transcription-polymerase chain reaction followed by Southern blot analysis. It was found that T cells constitutively expressed mRNA specific to T helper 1 cytokines (interleukin-2, interferon-gamma, tumor necrosi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 17 publications
1
5
0
Order By: Relevance
“…IL-5. The prominent role of AP-1 in IL-4 signaling has previously been shown by our group [4, 20]. Together, this is the first evidence showing that rolipram suppressed IL-4 signaling via functional suppression of AP-1 activation.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…IL-5. The prominent role of AP-1 in IL-4 signaling has previously been shown by our group [4, 20]. Together, this is the first evidence showing that rolipram suppressed IL-4 signaling via functional suppression of AP-1 activation.…”
Section: Discussionsupporting
confidence: 82%
“…We have previously shown that AP-1 is a prominent transcription factor in T cells in response to IL-4 [4, 20]. Therefore, we next checked modulations of AP-1 activation by rolipram.…”
Section: Resultsmentioning
confidence: 99%
“…Involvement of the H1-receptor was further ruled out by showing that the inducing effect of TNF-a and TPA, and the inhibitory effect of mizolastine and desloratadine were not significantly modified after overexpression of this receptor. Previous studies with second-generation H1-receptor antagonists have reported that they can diminish DNA binding of NF-kB [17][18][19] or AP-1 [40], but as opposed to the present work, involvement of the H1-receptor was not investigated.…”
Section: Discussionmentioning
confidence: 64%
“…It has been shown that some H1‐receptor antagonists inhibit Th2 cytokine production in several experimental conditions [51–53]. Accordingly, application of these drugs may modulate Th1/Th2 cytokine imbalance.…”
Section: Immunomodulatory Effects Of H1‐receptor Antagonistsmentioning
confidence: 99%